Brand redefinition and communication plan for Grândola - Calado, Miguel Jesus Rito (2014)
This project was elaborated with the intention to build a communication plan for Grândola, and its wide offer, in order to draw more tourists to the municipality. Grândola is located in South-west Portugal, being mostly known for an offer of Sun and Sea, with beaches that extend for 45 Km, but it also has rural tourism component, with green and calm landscapes, making it a close to nature destination. It also has the excitement of several events and a Casino. By analyzing the market and the current communication strategy, some points needing improvement were found, not only regarding this operational marketing vertex , but also in what concerns brand identity. With this in mind, this project is a proposal for: the redefinition of the brand Grândola, with the creation of a new image allows its affirmation, in order to be better recognized in the market; a communication plan that follows the constructed identity, where multiple marketing communication tools are used, being all aligned. This municipality has been able to grow in the tourist industry in the last few years, but still falls behind some other national offers that have more notoriety. However, it has the best performance in the region it is inserted, Alentejo Litoral. Knowing that, this project is based on the need to grow even more.